Melioidosis in an infant presenting with Eschar-like lesion: A Diagnostic Dilemma - Pragathesh Palaniappan; Reema Dakua; Ritu Singh; Vinita Shaju; Sravani Tera (Pediatric Sciences Journal, 2025)
Melioidosis, caused by Burkholderia pseudomallei, is an uncommon but serious infection in children and is predominantly reported in endemic regions, such as Southeast Asia and northern Australia. Melioidosis is known for its varied clinical spectrum of manifestation, which can range from mild to life-threatening presentations. Although pneumonia and septicemia are the most frequent presentations, cutaneous manifestations can also occur. These skin manifestations often mimic other tropical diseases, making diagnosis challenging, especially in resource-limited settings. Here, we describe a case of an infant from Andaman and Nicobar Islands, India, who presented with fever, respiratory distress, purulent ear discharge, diarrhea and an eschar-like skin lesion resembling scrub typhus. Given the initial clinical presentation, rickettsial infections were considered; however, blood culture confirmed Burkholderia pseudomallei as the causative agent. The patient was successfully managed with an extended course of intravenous meropenem and oral trimethoprim- sulfamethoxazole, which led to full recovery. This case underscores the importance of recognizing melioidosis as a differential diagnosis in endemic areas, particularly in children presenting with atypical skin lesions mimicking other febrile illnesses. Enhanced clinical awareness, coupled with improved diagnostic capabilities and timely initiation of appropriate antimicrobial therapy, is crucial for the effective management of melioidosis. This is particularly vital in regions where the disease remains underreported, and its true burden may be underestimated.